2018 IEEE International Symposium on Information Theory (ISIT) 2018
DOI: 10.1109/isit.2018.8437561
|View full text |Cite
|
Sign up to set email alerts
|

Repairing the Faure-Loidreau Public-Key Cryptosystem

Abstract: A repair of the Faure-Loidreau (FL) public-key code-based cryptosystem is proposed. The FL cryptosystem is based on the hardness of list decoding Gabidulin codes which are special rank-metric codes. We prove that the recent structural attack on the system by Gaborit et al. is equivalent to decoding an interleaved Gabidulin code. Since all known polynomial-time decoders for these codes fail for a large constructive class of error patterns, we are able to construct public keys that resist the attack. It is also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…One can also observe that the derived lower bounds on the work factor give a good estimate of the actual runtime of the algorithm denoted by W Sim . The results in Table 1 show further, that for parameters proposed in [19,33], the new algorithm solves Problem 2 with a significantly lower computational complexity than the approaches based on the known algorithms.…”
Section: Examples and Simulation Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…One can also observe that the derived lower bounds on the work factor give a good estimate of the actual runtime of the algorithm denoted by W Sim . The results in Table 1 show further, that for parameters proposed in [19,33], the new algorithm solves Problem 2 with a significantly lower computational complexity than the approaches based on the known algorithms.…”
Section: Examples and Simulation Resultsmentioning
confidence: 85%
“…The security of the public-key cryptosystem from [2] relied on the hardness of ML decoding of RS codes but was broken by a structural attack. More recently, some public-key cryptosystems based their security partly upon the difficulty of solving the problem Dec-Gab (Decisional-Gabidulin defined in the following) and Search-Gab (Search-Gabidulin), i.e., decoding Gabidulin codes beyond the unique decoding radius or derived instances of this problem [8,19,33].…”
Section: Introductionmentioning
confidence: 99%
“…Another important distance function of coding theory is the rank metric, which measures the rank of the difference between a pair of matrices with entries from a finite field F q . Rank metric codes have seen a recent resurgence of interest both for their potential use in code based cryptography and as error-correcting codes in network communications [19,26,27,36,39,40]. They are also intriguing as mathematical objects in their own right, and several researchers have sought to describe their structural properties [1,4,7,12,13,14,20,21,25,32,35].…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Gaborit et al showed, that the private key in the FL crytposystem can be recovered in polynomial time from the public key with high probability. In [7] it was shown, that the attack from [8] is equivalent to the problem of list decoding interleaved Gabidulin codes [9]. In other words, the private key is a noisy codeword of an interleaved Gabidulin code with error weight chosen slightly larger then the unique decoding radius.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of decoding is called probabilist unique decoding. By restricting to error patterns that make the probabilistic unique decoder of an interleaved Gabidulin decoder fail, the FL cryptosystem can be repaired [7].…”
Section: Introductionmentioning
confidence: 99%